Microstructure and intergranular corrosion resistance of UNS S17400 (17-4PH) stainless steel - Tavares, Sérgio Souto Maior (2010)
UNS S17400 or 17-4PH is a precipitation hardening martensitic stainless steel with many industrial appli cations. Quite different mechanical properties can be produced in this material by varying the aging tem perature. In this work, the influence of aging temperature on the intergranular corrosion susceptibility was evaluated by electrochemical and metallographic tests. The microstructural features were investi gated by X-ray diffraction, optical and scanning electron microscopy. Intergranular chromium carbide precipitation occurs in specimens aged at high temperatures, although NbC carbides were also observed. The results obtained by double loop electrochemical potentiodynamic reactivation tests (DL-EPR) show that the susceptibility to intergranular corrosion resistance increases with the increase of aging temper ature. Healing due to Cr diffusion in the 600–650 C range was not observed by DL-EPR tests